Determination of Isoflavone Content in SRM 3238 Using Liquid Chromatography-Particle Beam/Electron Ionization Mass Spectrometry - Zhang, Lynn X. (J AOAC Int, 2015)
The characterization of marker components in botanical materials is a challenging task and the increased consumption of botanicals and dietary supplements demands a greater understanding of the associated health benefits and risks. In order to successfully acquire and compare clinical results and correlate health trends, accurate, precise, and validated methods of analysis must be developed. Presented here is the development of a quantitative method for the determination of soy isoflavones (daidzin, glycitin, genistin, daidzein, and genistein) using liquid chromatography-particle beam/electron ionization mass spectrometry (LC-PB/EIMS). An internal standard (IS) approach for quantitation using 7-hydroxy-4-chromone as the IS compound was employed, with response factors for each individual isoflavone obtained from calibrant solutions. The results from this method were compared with the certified and reference values for NIST SRM 3238 Soy-Containing Solid Oral Dosage Form to demonstrate that the method was in control. Results obtained using LC-PB/EIMS were consistent with the NIST certified or reference values and their uncertainties for all five isoflavones, demonstrating that the LC-PB/EIMS approach is both accurate and precise when used for the determination of the target isoflavones in soy-containing dietary supplement finished products, while simultaneously providing structural information.